Completing the triad: synthesis and full characterization of homoleptic and heteroleptic carbonyl and nitrosyl complexes of the group VI metals. Issue 14 (20th March 2020) - Bohnenberger, Jan; Schmitt, Manuel; Feuerstein, Wolfram; Krummenacher, Ivo; Butschke, Burkhard; Czajka, Jakub; Malinowski, Przemysław J.; Breher, Frank; Krossing, Ingo
Abstract : The triad of group VI metalloradicals is now finally accessible via the oxidation of Cr/Mo/W(CO)6 with the synergistic oxidative system Ag[F-Al(OR F )3 2 ]/0.5 I2 . Abstract : Oxidation of M(CO)6 (M = Cr, Mo, W) with the synergistic oxidative system Ag[WCA]/0.5 I2 yields the fully characterized metalloradical salts [M(CO)6 ] + ˙[WCA] − (weakly coordinating anion WCA = [F-Al(OR F )3 2 ] −, R F = C(CF3 )3 ). The new metalloradical cations with M = Mo and W showcase a similar structural fluxionality as the previously reported [Cr(CO)6 ] + ˙. Their reactivity increases from M = Cr < Mo < W and their syntheses allow for in-depth insights into the properties of the group 6 carbonyl triad. Furthermore, the reaction of NO + [WCA] − with neutral carbonyl complexes M(CO)6 gives access to the heteroleptic carbonyl/nitrosyl cations [M(CO)5 (NO)] + as salts of the WCA [Al(OR F )4 ] −, the first complete transition metal triad of their kind.